ADB fifth decade 2007 - 2016. (Metro Manila, Philippines Asian Development Bank, 2017)
This fifth volume from the series ADB through the Decades presents ADBs response to intensified development challenges, a more ambitious global development agenda, and the emergence of new sources of development finance.
Keywords: Public administration -- Developing countries..; Electronic books